Pengembangan Media Pembelajaran Berbasis Assemblr Edu Pada Materi Bangun Ruang - Bonita, Cindy Condolisa; Yuyun Elizabeth Patras; Rukmini Handayani (JKPD (Jurnal Kajian Pendidikan Dasar), 2025)
Design, Development, Implementation, and Evaluation) aimed at developing Assemblr Edu learning media and improving learning outcomes, especially in spatial geometry material. Validation of learning media was carried out by four experts, namely media experts, language experts, lecturer material experts, and teacher material experts. There is an average media validation result of 90%, language validation of 92.7%, material validation by lecturers of 96.6%, and material validation by teachers of 88% with an average overall result of 91.8% with very feasible criteria. There is an N-Gain value with an average score of 0.83 with high criteria. There are student questionnaire response results with an average of 90.8% with very good criteria and teacher questionnaire responses of 88.3% with very good criteria. The results can be concluded that learning media using the Assemblr Edu platform is very feasible and effective in improving student learning outcomes, especially in mathematical spatial geometry material.